Effect of Coiling and Macrobending on Fiber To The Building (FTTB) Network Activation - Yustini, Yustini; Nasrul, Nasrul; Asril, Aprinal Adila; Nugraha, Bintang Aulia (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Fiber to the Building (FTTB) provides a fast and efficient service. However, the network quality may be affected by high attenuation at the termination (ONU) due to coiling, macrobending, and the length of patch cords, impacting network stability. This study aims to measure and analyze the effect of coiling and macrobending on patch cord cables of different lengths, as well as their influence on attenuation and FTTB network performance. The method includes simulating patch cord cables with lengths of 3m, 5m, and 10m. The tested treatments include conditions without coil, with coil, macrobending without coil, and macrobending with coil applied to the final termination before and after activating the FTTB network. Before activation, the lowest attenuation was 19.78 dB in the 3m cable without coil and macrobending, while the highest attenuation was 21.93 dB in the 10m cable with 5 coils (6cm curvature) and macrobending (0.8cm diameter). After activation, the lowest attenuation was 19.74 dB in the 3m cable without coil and macrobending, while the highest attenuation was 23.92 dB in the 10m cable with 5 coils (6cm curvature) and macrobending (0.8cm diameter). The test results show that the attenuation is affected by the number of coils, macrobending, and cable length.Damping increases with an increase in coils, cable length, and macrobending.